A4NH 2019 annual report highlights: Flagship 4 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
This includes three highlights document for Flagship 4 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Unpacking the focus on stunting in solving global nutrition challenges Highlight 2: Engaging in global conversations on diets and nutrition Highlight 3: Building capacity at the national level to address malnutrition